ANTROPOLOGI GENDER DALAM PEMBAGIAN KERJA SECARA SEKSUAL MASYARAKAT NELAYAN - Nur Iza Dora (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2017)
This study was conducted on fisherman community at Percut Village, Percut Sei Tuan, Deli Serdang Regency, North Sumatera Province. Focus of this study was to describe woman involvement on public sector by working as fisherwoman and what their strategies are in building household economy. Aim of the research is to describe fisherwoman’s life at Percut Village. Approach used was qualitative approach with data collecting through participated observation and in-dept interview.